JGP : Journal of Goverment and Politics Vol.8 No.1 February 2017 - Redaksi (Fak. Sosial & Ilmu Politik UMY, 2017)
- Do Productive Government Expenditures Affect Economic Growth? Evidence from Provincial Governments across Indonesia - Moving towards a normalised path: political islam in contemporary indonesia -...